A Study of Platelet Functions with a New Analyzer Using High Shear Stress (PFA100™) in Patients Undergoing Coronary Artery Bypass Graft - Lasne, Dominique; Fiemeyer, Annick; Chatellier, Gilles; Chammas, Carine; Baron, Jean-François; Aiach, Martine (Thrombosis and Haemostasis, 2000)
Platelet dysfunction can be a major factor in excessive bleeding following cardiopulmonary bypass (CBP). A rapid, specific and sensitive method to identify platelet dysfunction would be a useful tool for identifying patients at an increased risk of bleeding. The ability of PFA100™, an in vitro bleeding test, to predict increased bleeding risk linked to platelet dysfunction was tested in 146 patients undergoing primary coronary artery bypass graft. Blood samples were taken the day before surgery, and 15 min and 5 h after heparin neutralization. The preoperative closure times (CT), i. e. the time required for platelets in citrated whole blood to occlude an aperture cut into a membrane coated with collagen plus either epinephrine (CTEPI) or adenosine diphosphate (CTADP) were longer in blood-group-O patients than in patients with other groups. The 15 min postoperative values were significantly longer from preoperative values essentially owing to CBP-induced hemodilution. Interestingly, 5 h after CBP, a significant reduction in CT values probably reflected platelet hyperaggregability. No correlation was found between calculated blood loss (CBL) and either preoperative or postoperative PFA values.
Keywords: Platelet function; cardiopulmonary bypass; PFA100™; in vitro bleeding time